FEASIBILITY PERFORMANCE OF CANDLENUT (ALEURITES MOLUCCANA) FARMING (CASE STUDY OF CANDLENUT FARMERS IN LABALIMUT VILLAGE): KERAGAAN KELAYAKAN USAHATANI KEMIRI (Aleurites moluccana) (STUDI KASUS PADA PETANI KEMIRI DI DESA LABALIMUT) - Abdan Sakuro; Ema Hilma Meilani; Neneng Kartika Rini (PT. ROCE WISDOM ACEH, 2026)
This study aims to analyze the feasibility of candlenut farming (Aleurites moluccana) in Labalimut Village, Nagawutung District, Lembata Regency, East Nusa Tenggara Province. The method used is a descriptive, quantitative approach, with simple random sampling involving 36 candlenut farmers. The results show that the average revenue is IDR 16,791,667 per hectare, with total production costs amounting to IDR 1,259,167 per hectare, resulting in an income of IDR 15,532,500 per hectare. The R/C ratio value of 13.61 (greater than 1) indicates that candlenut farming is feasible and profitable. The break-even point BEP of production is 41.97 kg, the BEP price is IDR 2,739 per kg, and the BEP revenue is IDR 27,639. Therefore, candlenut farming in this region has strong economic prospects and potential for further development.